The Impact of The Coalition of Arab States Intervention on The Humanitarian Crisis in Yemen Internal Conflict - Rasbil, Nurul Annisa; Burhanuddin, Agussalim; Seniwati , Seniwati (Faculty of social and Political sciences, Hasanuddin University, 2024)
The civil war that erupted in Yemen in 2015 caused the creation of the worst humanitarian crisis in Yemen's history, and this humanitarian crisis is also categorized as the worst humanitarian crisis in the history of modern humanity. The coalition of Arab countries became one of the actors involved in Yemen's civil war after receiving a request for military intervention from President Hadi over the threat of a coup carried out by the Houthis. The coalition of Arab states then carried out a military operation into Yemeni territory aimed at eliminating the threat posed by the Houthis and restoring President Hadi's government as the official government of the Yemeni state. However, the military operation carried out by the coalition of Arab countries is considered the beginning of the worst humanitarian crisis in Yemen's history. This research then aims to analyze the impact of the involvement caused by the coalition of Arab countries on the humanitarian crisis in Yemen's civil war.